The Potential of Concentrate of Fermented Milk for Natural Antibacterial - Putri Dian Wulansari; Novia Rahayu; Firgian Ardigurnita (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The objective of the study was to investigate the potential of concentrated fermented milk (yoghurt and kefir) from cow milk and goat milk as a natural antibacterial ingredient. Completely randomized factorial design 2x2 was used in this research. The first factor was the type of fermentation (yoghurt and kefir) and the second factor was type of milk (cow milk and goat milk). The parameters measured were composition, inhibitory test, chemical and physical test. The results showed that the type of milk had significantly affected (P<0.05) on amount of whey and antibacterial activity. Type of fermentation and milk type have a significant effect (P<0.05) on concentrate. Concentrated fermented goat milk has the higher resistance to S. aureus bacteria than concentrated fermented cow milk on the inhibitory test. The type of fermentation and milk type has no significant effect on the composition (moisture content and total solids) and chemical characteristics (pH, lactic acid and free fatty acids) of the concentrate and whey. The conclusion of this research is goat milk yoghurt concentrate was potential to used as a natural antibacterial material.